Ethics and scientific research: a perspective based on the process of scientific publication - Rozo Castillo, Jairo A. (2019)
The purpose of this article is to expand the taxonomy of the most frequent ethical misconducts currently found in scientific publications. We present examples of fraud in contrast to an ethical conduct in research and publications arising from research. Then, we show the taxonomy in different stages: before, during and after the publication. Before the publication, the following ethical misconducts were found: conflicts of interest not declared by the authors, undeserved or insufficient authorship, salami slicing, plagiarism, self-plagiarism, fabrication, manipulation or impossibility of data replication, and parallel submission of articles. During the process of publication: conflicts of interest in peer review, false peer reviewers, theft of the manuscript by peer reviewers, content mishandling and undeserved authorship following peer review. After the publication: alteration of the impact factor. Next, we analyze the consequences of ethical misconducts for both authors and journals. Finally, we offer some alternatives to fight against these misconducts in the process of scientific publication to foster ethical integrity